Antidiabetic efficacy of sea fish oil in ameliorating hyperglycaemia by enhancing FFAR1, GLP-1 and inhibiting DPP-4 signalling in the pancreatic tissues of high lipid diet and streptozotocin-induced type 2 diabetic rats - Pyne, Shrabanti; Mandal, Meghamala; Das, Sanjay; Bhowmick, Supriya; Das, Koushik; Rao, J. Sreenavasa; Laha, Jayasree (Acta Biologica Szegediensis, 2023)
Eicosapentaenoic acid and docosahexaenoic acid are n-3 fatty acids that are highly available in sea-fishes. Many studies have revealed that n-3 fatty acids play antidiabetic activity. In this study antidiabetic activity of the three sea fishes oils, ‘volavetki’ (Panna microdon, Bleeker 1849), ‘ruli’ (Coilia dussumieri, Valenciennes 1848), and ‘tapra’ (Opisthopterus tardoore, Cuvier 1829), as well as three fresh-water fishes oils, ‘bata’ (Labeo bata, Hamilton 1822), ‘folui’ (Opisthopterus tardoore, Cuvier 1829), and ‘mourala’ (Amblypharyngodon mola, Hamilton 1822) evaluated high lipid diet (HLD) and STZ-induced type 2 diabetes mellitus (T2DM) rats. The GC-MS analysis revealed high n-3 fatty acid content in volavetki oil. Supplementation of sea-fish oils and antidiabetic effect was monitored by fasting plasma blood glucose and HbA1c. Also, insulin, c-peptide, glucagon-like peptide-1, dipeptidyl peptidase-4, free fatty acid receptor 1, glucokinase, glucose-6 phosphatase, superoxide dismutase, glutathione peroxidase, catalase, malondialdehyde, plasma total cholesterol, low density lipoprotein, triglycerides, high density lipoprotein, c-reactive protein, total protein, alkaline phosphatase, and histopathology of pancreatic tissues were evaluated. Out of six fish oils, oral supplementation with volavetki oil resulted in significant reduction of plasma blood glucose, HbA1c of T2DM rat. All other parameters in T2DM rats were returned to near normally by treatment of volavetki oil. These findings strongly indicate that volavetki oil possess antidiabetic activity.